Optical writing and single molecule reading of photoactivatable and silver nanoparticle-enhanced fluorescence. Issue 5 (5th March 2020) - Dogantzis, Nicholas P.; Hodgson, Gregory K.; Impellizzeri, Stefania
Abstract : We present a hybrid nano-molecular system for optically activated, silver nanoparticle enhanced fluorescence in solution and in thin-polymer films, alongside single molecule level insights into the metal-enhanced fluorescence mechanism. Abstract : We designed a hybrid nanoparticle–molecular system composed of silver nanostructures (AgNP) and a fluorogenic boron dipyrromethene (BODIPY) that can be selectively activated by UVA or UVC light in the presence of an appropriate photoacid generator (PAG). Light irradiation of the PAG encourages the release of p -toluenesulfonic, triflic or hydrobromic acid, any of which facilitate optical 'writing' by promoting the formation of a fluorescent species. Metal-enhanced fluorescence (MEF) by AgNP was achieved through rational design of the nano–molecular system in accordance with the principles of radiative decay engineering. In addition to increasing signal to noise, AgNP permitted shorter reaction times and low irradiance – all of which have important implications for applications of fluorescence activation in portable fluorescence patterning, bioimaging and super-resolution microscopy. Single molecule fluorescence microscopy provided unique insights into the MEF mechanism which were hidden by ensemble-averaged measurements, demonstrating that single molecule 'reading' is a valuable tool for characterizing particle–molecule interactions such as those responsible for the relative contributions of increased excitation and plasmophoric emission toward overall MEF. This work represents a step forward in the contemporary design of synergistic nano–molecular systems, and showcases the advantage of fusion between classic spectroscopic techniques and single molecule methods in terms of improved quantitative understanding of fluorophore–nanoparticle interactions, and how these interactions can be exploited to the fullest extent possible.